Drug-interactive mPEG-b-PLA-Phe(Boc) micelles enhance the tolerance and anti-tumor efficacy of docetaxel - Feirong Gong; Rongrong Wang; Zhengquan Zhu; Jiayao Duan; Xin Teng; Zhong-Kai Cui (Taylor & Francis Group, 2020)
Docetaxel (DTX) is one of the most promising chemotherapeutic agents for a variety of solid tumors. However, the clinical efficacy of the marketed formulation, Taxotere®, is limited due to its poor aqueous solubility, side effects caused by the emulsifier, and low selective DTX distribution in vivo. Here a facile, well-defined, and easy-to-scale up DTX-loaded N-(tert-butoxycarbonyl)-L-phenylalanine end-capped methoxy-poly(ethylene glycol)-block-poly(D,L-lactide) (mPEG-b-PLA-Phe(Boc)) micelles (DTX-PMs) were prepared in an effort to develop a less toxic and more efficacious docetaxel formulation. The physicochemical properties, pharmacokinetics, biodistribution, and in vivo anti-tumor efficacy were evaluated in comparison to the marketed DTX formulation Taxotere®. DTX was successfully encapsulated in the hydrophobic micellar core with a high encapsulation efficiency (> 95%) and a high drug loading capacity (4.81 ± 0.08%). DTX-PMs exhibited outstanding stability in the aqueous environment due to the strong interactions between the terminal amino acid residues and docetaxel. The pharmacokinetic study in Sprague-Dawley rats revealed higher DTX concentrations in both whole blood and plasma for the group treated with DTX-PMs than that treated with Taxotere® due to the improved stability of the micellar formulation. In human non-small cell lung cancer (A549) tumor-bearing Balb/c nude mice, DTX-PMs significantly improved DTX accumulation and stalled DTX elimination in tumors than in bone marrow. Furthermore, only by half of the DTX dosage, our DTX/mPEG-b-PLA-Phe(Boc) micelles can achieve similar therapeutic effects as Taxotere®. Altogether, DTX-PMs hold great promise as a simple and effective drug delivery system for cancer chemotherapy.